Lumbar bone marrow microcirculation measurements from dynamic contrast-enhanced magnetic resonance imaging is a predictor of event-free survival in progressive multiple myeloma - Hillengaß, Jens; Wasser, Klaus; Delorme, Stefan; Kießling, Fabian; Zechmann, Christian; Benner, Axel; Kauczor, Hans-Ulrich; Ho, Anthony Dick; Goldschmidt, Hartmut; Möhler, Thomas (Clinical cancer research, 2007)
Purpose: Dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) with high temporal resolution enables the detection of microcirculation variables amplitude A and exchange rate constant kep. In this study, the prognostic value of the DCE-MRI variables for overall survival and event-free survival in patients with progressive multiple myeloma was investigated. - Experimental Design: Between 1999 and 2001, 65 patients with progressive or relapse of multiple myeloma requiring therapy were investigated with DCE-MRI of the lumbar spine before start of therapy. The contrast uptake was quantified using a two-compartment model with the output variables amplitude A and exchange rate constant kep reflecting bone marrow microcirculation. The estimated median follow-up was 56 months. Event-free survival and overall survival were investigated for DCE-MRI variables and for established prognosis variables (β2-microglobulin, lactate dehydrogenase, albumin, and age). - Results: Using a multivariate Cox regression model, β2-microglobulin and amplitude A of DCE-MRI were identified as statistically significant prognostic variable of event-free survival with Ps of 0.01 and 0.02, respectively. A statistical correlation of DCE-MRI variables with overall survival could not be found. The multivariate analysis of β2-microglobulin, age, lactate dehydrogenase, and albumin revealed β2-microglobulin as statistically significant prognostic factor for overall survival in this group of patients (P < 0.001). - Conclusions: This analysis identifies contrast-enhanced DCE-MRI variable amplitude A reflecting increased bone marrow microcirculation and angiogenesis as a novel and possibly useful prognostic factor in patients with multiple myeloma. Prospective studies are currently done to further investigate this functional variable for prognosis and stratification of myeloma patients.
Gesehen am 02.11.2021